Kajian Filosofis atas Hak Asasi Alam Semesta (HAAS) dan Hak Asasi Manusia (HAM): Telaah Konsep Tafsir Terma Al-'Alamin's dalam Al-Qur'an (Institut Agama Islam Yasni Bungo, 2023)
This paper is intended to explore the holistic philosophy of al-ʿalamin in al-Qur’an as the basis for Universal Rights, Hak Asasi Alam Semesta (HAAS) for the lack of comprehensiveness of Human Rights, Hak Asasi Manusia (HAM) which tends to be anthropocentric-materialistic-secularistic. This research is a qualitative research that relies on the literature review method. The analytical tool used in this research is the Hermeneutical-philosophical paradigm of human rights and international law contained in the concept of al-ʿalamin. Al-ʿalamin, God Sustainer of Humans, has been, is, will always be translated and interpreted, with the embodiment in the form of HAM. Not only human rights, it also needs to be conceptualized and implemented in the discourse of HAAS, God is the Custodian of the Universe. HAM does not necessitate human religiosity. It is just the fulfillment of human rights to one creature, named human. HAI, in addition to fulfilling human rights religiously and spiritually, is also primarily a blessing for the universe, including the fulfillment of human rights for all forms of natural resources, such as plants, animals, jinn, earth, planets, galaxies and so on. Therefore, the five main things that make up maqashid al-shari'ah, namely protecting religion, soul, lineage, property and mind, which have an anthropocentric tendency, become more holistic when fulfilled by protecting the universe, hifz al-ʿalamin.